Study on Hygiene and Sanitation and the Presence of Escherichia coli in the Tofu Industry - Khodijah Nur Chasanah; Adian Khoironi; Slamet Isworo (BIORE Scientia Publisher, 2025)
The ineffectiveness of hygiene and sanitation standards in the food industry, including the tofu industry in Indonesia, remains a significant issue. This condition increases the risk of Escherichia coli (E. coli) contamination, which can negatively impact public health. This study aims to provide an in-depth understanding of hygiene and sanitation practices in tofu businesses in Jomblang, Semarang City, and serve as a basis for improving food safety and hygiene standards. A descriptive quantitative approach was used, with data collected through interviews, observations, and laboratory tests. The analysis revealed that many hygiene aspects, such as equipment and raw material handling, did not meet the required standards, posing a risk of microbial contamination. Laboratory tests confirmed the presence of Escherichia coli in tofu soaking water samples, indicating potential health hazards for consumers. The implementation of hygiene and sanitation principles in food production must be optimized to improve product quality and prevent the spread of infectious diseases.